Studi Populasi Mikrob Fungsional pada Tanah Gambut yang Diaplikasikan Dua Jenis Pestisida - MAIPA DIA PATI; SYAIFUL ANWAR; RAHAYU WIDYASTUTI; DADANG . (Departemen Biologi, Institut Pertanian Bogor, 2016)
Agricultural land expansion necessity for food security in Indonesia has been faced by the fact in utilizing marginal land such as shallow peat soil in Central Kalimantan. Among problems encountered in such marginal land are pests and diseases incidence. Farmers practice in dealing with those problems is the chemical pesticides application. Unintended chemical pesticides that fall on/into the soil might have an adverse effect to soil microbes activity. This research aimed to assess the effect of pesticides on functional soil microbes population in peat soil. The research used completely randomized factorial design with two factors. First factor was 7 combinations of types (paraquat and buthylphenylmethyl carbamat (BPMC)) and dosages (50, 100, and 200% of recommended dosage) of pesticides. Second factor was 4 incubation times (1, 7, 14, and 28 days). Following the each of incubation times, the soil samples treated and analyzed for population of phosphate solubilizing microbes, cellulolytic microbes, and N2 fixing bacteria. The results show that phosphate solubilizing fungi population decrease by pesticides treatment. In contrast, pesticides significantly increased the Azospirillum population. Adverse effect to microbes population was found on the first day of incubation, however it recovered at 7 days and longer incubation times. In general, functional microbes population with paraquat application lower than BPMC application.